Comparison of CE‐MS/MS and LC‐MS/MS sequencing demonstrates significant complementarity in natural peptide identification in human urine. Issue 7 (20th November 2013) - Klein, Julie; Papadopoulos, Theofilos; Mischak, Harald; Mullen, William; Phillips, Terry M.
<x xml:space="preserve">Abstract</x> Clinical proteomics has led to the identification of biomarkers specifically associated with a clinical condition that can serve for diagnostic or prognostic purposes. Learning more about the origin of these protein fragments would lead to a better insight in the pathology, and this requires improved identification of the peptide sequences. The aim of this study is to assess the complementarity of LC‐MS/MS and CE‐MS/MS as techniques in peptide sequence identification of the urinary low‐molecular weight proteome. A male standard human urine sample was analyzed using LC‐ and CE‐MS/MS (n = 10 per technique), identifying 905 unique peptide sequences with high confidence, 50% of those were identified only with LC, 20% only with CE and 30% with both techniques. Higher LC coverage might be due in part to the higher amount of sample that can be loaded onto an LC column. Peptides uniquely identified in CE are generally small and highly charged, likely unable to bind to the LC column In conclusion, we showed that LC‐MS/MS and CE‐MS/MS are highly complementary in identifying peptide sequences. The combination of both technologies results in significantly increased sequence coverage.